APUNTES DE COYUNTURA: Critical Observations on Climate Change, from a Bribri Indigenous Woman (Revista Rupturas, 2016)
This paper was first presented on November 12th, 2015, during the First UNED Encounter: Management, Climate Change and Social Participation; specifically at the Unofficial Perspectives: Paradigmatic Challenges and Community Proposals panel, organized by the Research Center on Culture and Development (CICDE, for its acronym in Spanish). Given that 2016 was declared by the National Council of Rectors (CONARE, for its acronym in Spanish) as the year of Public Universities for Mother Nature, the Journal Rupturas considers it relevant to publish this document in its section: Annotations on the Juncture, while preserving the style of the author.
Keywords: Indigenous woman; climate change; critique; recommendations; ecological consciousness